IMPLEMENTASI KEBIJAKAN RETRIBUSI PELAYANAN PARKIR TEPI JALAN UMUM DI BANGKINANG KOTA - Putra, Ikhsan Risniawan; ", Zulkarnaini (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Kampar regency has a high population with its main base in Bangkinang Kota. The large population of Kampar Regency is accompanied by the high number of four-wheeled vehicles and two wheels as a device to facilitate in carrying out daily activities. Personal vehicles require a temporary stop place with a certain period of time and left by the driver in the form of parking facilities. This is one of the potentials owned by the Bangkinang Kota from parking fees to support LOR (Local Own Revenue) managed by the Department of Transportation Kampar regency. The concept of theory used is the theory of Policy Implementation according to Van Meter and Van Horn in Agustino has (6) variables namely, objectives and targets of policies, resources, implementing characteristics, executor attitude, communication antaorganization and social / political / economic environment. Then for factors influencing policy implementation based on the findings or observations of authors at the scene. This research uses qualitative method with descriptive data assessment. The result of the research indicates that there are some obstacles in the implementation process of public roadside retribution policy in bangkinang kota such as insufficient human resources, public participation is not maximized, lack of firmness of parking coordinator in cracking down parking mistress. Then there are some obstacles found in the factors that influence the policy of public roadside retribution levies in the bangkinang kota such as supervision has not been maximized and socialization or banners of appeals that have not been effective.Keywords: Policy Implementation, Retribution, Public Roadside Parking